Characteristics and Physical Stability of Nanoemulsion as a Vehicle for Anti-Aging Cosmetics: A Systematic Review - Eva Syariefah Rachman; Widji Soeratri; Tristiana Erawati M (Universitas Airlangga, 2023)
Background: Skin aging can be overcome by applying anti-aging cosmetics. Many active ingredients that have anti-aging potential are derived from plants, and these materials must be delivered with a sound skin delivery system, namely nanoemulsion. The characteristics of nanoemulsion are closely related to physical stability. Objective: This study aims to conduct a systematic review of in vivo and in vitro study designs to examine the characteristics and physical stability of nanoemulsions used in topical anti-aging cosmetics. Methods: A systematic literature review based on the PRISMA statement was used to review the articles regarding nanoemulsions' characteristics and physical stability. The article search was accessed from an internet search database: Scopus, Pubmed, and Web of Science, published between January 2012 and June 2022. Results: Of the 244 articles, 44 were found to be related to the characteristics and physical stability of nanoemulsions in anti-aging cosmetics. These showed that active ingredients with antioxidant activity, filter UV rays, moisturizing agents, and cell-repairing agents are delivered by a nanoemulsion system with various types and ratios of surfactants, cosurfactants, and oil phases. Tween 80, Span 80, Transcutol HP, and Caprylic/capric triglyceride are the most widely used nanoemulsion compositions. Conclusion: The type and composition of the oil phase, surfactant, and cosurfactant affect the characteristics of the nanoemulsion (droplet size, polydispersity index, viscosity, zeta potential) and the physical stability of the nanoemulsion so that it can deliver active ingredients that have the potential as anti-aging well.